Changing faces of Slovenia - Vobič, Igor (Javnost (Ljubljana), 2014)
The study indicates that political, economic and social faces of Slovenia have changed substantially during the half-decade of the crisis. While the ability of citizens to influence important political decisions has been curtailed on both the national and transnational level, instability has become endemic and social solidarity has been eroded. By using quantitative and qualitative content analysis the study analyses how the unfolding crisis has been communicated in the media in the 2008-2013 period with respect to the dynamics between structure and agency as well as regarding the key (inter)national features and contours of the crisis. The study indicates Slovenian news media hardly served as an integrative force and a common forum for an inclusive and open debate. Namely, results of the quantitative content analysis indicate that journalism communicated the "causes" for the crisis by portraying it as something purely accidental, while rarely pointing at the possibility of its systemic nature. Similarly, "solutions" have been predominantly portrayed within the prevailing paradigms or through the neoliberal prism favoured by holders of political and economic power. Qualitative content analysis of how Slovenian news media communicated the decisive breaks and formative moments of the unfolding crisis shows they mostly relied on event orientation, simplistic juxtapositions and naturalisation of the established power divisions on national as well as international levels.
Keywords: Slovenia; Slovenija; ekonomska kriza; ekonomski položaj; družbene razmere; mass media; množični mediji; informiranje